2000
DOI: 10.1046/j.1460-9568.2000.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive overactivation of protein kinase C in guinea pig brain increases α‐secretory APP processing without decreasing β‐amyloid generation

Abstract: Whilst it is generally accepted that the activation of protein kinase C (PKC) increases amyloid precursor protein (APP) secretion in vitro, the role of PKC in the regulation of APP processing and beta-amyloid generation in vivo is still not well understood. In order to address this question, we established the animal model of neocortical microencephalopathy in guinea pigs caused by in utero treatment with methylazoxymethanol acetate, a DNA-methylating substance that eliminates proliferating cells of neuroepith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 60 publications
5
29
1
Order By: Relevance
“…Moreover, in two other studies (Levites et al, 2002(Levites et al, , 2003, EGCG was found to modulate PKC activity and to consequently increase secreted levels of sAPP-␣, further supporting this conclusion. However, these studies failed to measure the effects of EGCG on A␤ generation, which is important given that secretion of sAPP-␣ can be regulated independently of A␤ production (Rossner et al, 2000). Our data show that EGCG both promotes ␣-secretase activity and attenuates A␤ production, thereby augmenting nonamyloidogenic APP processing.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Moreover, in two other studies (Levites et al, 2002(Levites et al, , 2003, EGCG was found to modulate PKC activity and to consequently increase secreted levels of sAPP-␣, further supporting this conclusion. However, these studies failed to measure the effects of EGCG on A␤ generation, which is important given that secretion of sAPP-␣ can be regulated independently of A␤ production (Rossner et al, 2000). Our data show that EGCG both promotes ␣-secretase activity and attenuates A␤ production, thereby augmenting nonamyloidogenic APP processing.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, it is often inferred that extracellular elevation of sAPP-␣ (resulting from nonamyloidogenic pathway activation) can be taken as indirect evidence of inhibition of BACE and the associated amyloidogenic pathway. However, because the extracellular secretion of these various fragments can be regulated independently of APP cleavage, it is important to fully characterize the effects of treatment on both pathways concurrently before making inferences about underlying mechanisms (Rossner et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent study showed that Par-4 interacts with the regulatory domains of the and forms of protein kinase C and inhibits their enzyme activity (24). The possible implications of these interactions in APP processing need to be examined carefully because several studies have indicated that protein kinase C-dependent pathways might participate in regulation of APP processing (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The data are consistent with several reports showing a dissociation between sAPPα release and Aβ generation both in vitro or in vivo (Loefler and Huber, 1993;Querfurth et al, 1994;Dyrks et al, 1994;LeBlanc et al, 1998;Rossner et al, 2000), suggesting that there might be a more complex regulatory mechanism of these two processing events of APP. For instance, constitutive activation of PKC in guinea pig brain increased sAPPα secretion without any effect on secreted Aβ (Rossner et al, 2000), suggesting that the α--and β--secretase pathways may be differentially controlled. Because Yu et al, (2010) examined the effects of Mg only on the pathologically high production of Aβ, the modulation of the physiological Aβ production by Mg needs to be established in future studies.…”
Section: Magnesium In Adsupporting
confidence: 92%
“…It also has been shown that intra--cerebroventricular administration of secreted forms of sAPPα to amnestic mice has potent memory--enhancing effects and blocks learning deficits induced by scopolamine (Meziane et al, 1998 (Yu et al, 2010). The data are consistent with several reports showing a dissociation between sAPPα release and Aβ generation both in vitro or in vivo (Loefler and Huber, 1993;Querfurth et al, 1994;Dyrks et al, 1994;LeBlanc et al, 1998;Rossner et al, 2000), suggesting that there might be a more complex regulatory mechanism of these two processing events of APP. For instance, constitutive activation of PKC in guinea pig brain increased sAPPα secretion without any effect on secreted Aβ (Rossner et al, 2000), suggesting that the α--and β--secretase pathways may be differentially controlled.…”
Section: Magnesium In Adsupporting
confidence: 84%